Human papillomavirus (HPV) origin-binding protein associates with mitotic spindles to enable viral DNA partitioning - Van Tine, Brian A. (National Academy of Sciences, 2004)
Human papillomaviruses (HPVs) establish long-term infections in patients. The mechanism for extrachromosomal HPV DNA persistence in cycling cells is unknown. We show that HPV origin-containing plasmids partition as minichromosomes, attributable to an association of the viral origin recognition protein E2 with mitotic spindles. α-, β-, and γ-tubulins were pulled down with a tagged E2. The N-terminal transacting and C-terminal protein dimerization/DNA binding domains independently associated with the spindles. We suggest that this E2 property enables these viruses to establish persistence. Its implication for HPV oncogenesis is presented.